The Legal Issues in Implementing Constitutional Court Decision Number 49/PUU-IX/2011 (The Polemic of the Abolition of Law 7/2020 Article 59 Paragraph 2) - Syaidi, Ridwan (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2024)
According to Shaw et.al. (2018) the constitutional court is one of the forces behind the revival of comparative studies of constitutional law in the last two decades. The establishment of a constitutional court as the main feature of constitutional reform in new democracies. The purpose of this research is to find out the form of the decision Number 49/Puu-IX/2011 regarding the abolition of Article 59 paragraph 2 of Law Number 7 of 2020, and to find out the impact of Number 49/Puu-IX/2011 concerning the abolition of Article 59 paragraph 2 of the Law. - Law number 7 of 2020?. The method used is normative juridical because it discusses a decision of Law number 7 of 2020 concerning article 59 paragraph 2 which is deleted. The results of the study show 1) Decision Number 49/Puu-IX/2011 which deletes the Manuscript Law 7/2020 Article 59 paragraph (2). 2) The provisions in Article 59 Paragraph (2) were deleted in the results of the revision of the Constitutional Court Law or Law Number 7 of 2020 which was ratified by the DPR. This decision has a polemic impact on the community because it is considered a scenario for the DPR and the President to submit the Constitutional Court's decision, so that the DPR and the President no longer have an assessment of the Constitutional Court. The public considers that this decision is related to the work copyright law because with the abolition of article 59th paragraph 2 it can allow everything that is abolished in the work copyright law to be in vain because it is still under the authority of the president and the DPR.